Changes in soil microbial communities due to biological invasions can reduce allelopathic effects. Issue 5 (27th February 2017) - Li, Yang‐Ping; Feng, Yu‐Long; Kang, Zong‐Li; Zheng, Yu‐Long; Zhang, Jiao‐Lin; Chen, Ya‐Jun
Summary: Soil microbes are important in mediating allelopathic interactions between invasive and native plants in the field. However, it was not known how these interactions vary in the process of biological invasions and the effects of soil microbes; this knowledge may facilitate understanding the dynamics and mechanisms of biological invasions and managing invaded ecosystems. We conducted competition and seed germination experiments to determine the allelopathic effects of Ageratina adenophora in soils from 42 sites with varying abundances of the invasive plant. Then we isolated the microbes that could degrade the allelochemicals of the invasive plant and tested their functions. In both experiments, the allelopathic effects of the invasive plant were much stronger in soils from non‐invaded sites than in soils from invaded sites. Activities of the allelochemical‐degrading microbes were higher and degradation of the allelochemicals of the invasive plant was faster in soils from invaded sites than in soils from non‐invaded sites. In living soils from 30 sites with increasing abundance of A. adenophora, the allelopathic effects of the invasive plant decreased and degradation of the allelochemicals and activity of the allelochemical‐degrading microbes gradually increased. Two bacterial strains were isolated from the soils. Inoculation of Arthrobacter sp. ZS, which was isolated from soil invaded by A. adenophora, greatly increased the degradation of the allelochemicals, thereby decreasing its allelopathic effects. Synthesis and applications . Our results indicate that soils may accumulate microbes that can degrade allelochemicals in the process of biological invasions, gradually reducing the allelopathic effects of invasive species. The effects of soil microbes should be considered when studying dynamics and mechanisms of biological invasions. Application of allelochemical‐degrading microbes may facilitate ecological restoration of invaded or newly disturbed ecosystems by alleviating allelopathic inhibition of invasive plants on native plants. Abstract : Our results indicate that soils may accumulate microbes that can degrade allelochemicals in the process of biological invasions, gradually reducing the allelopathic effects of invasive species. The effects of soil microbes should be considered when studying dynamics and mechanisms of biological invasions. Application of allelochemical‐degrading microbes may facilitate ecological restoration of invaded or newly disturbed ecosystems by alleviating allelopathic inhibition of invasive plants on native plants.